Adaptasi Hunian di Dalam Kawasan Dengan Kebisingan Tinggi: case study: the settlement of Maleber Utara Street - Monica Dewi; Agus Suharjono Ekomadyo (EMARA: Indonesian Journal of Architecture, 2020)
Settlement along Maleber Utara street is a unique case of settlement with a unique condition:it conjuncts with three known noise sources; road traffic, railway traffic, and air traffic. The ideal house is a house in a tranquil environment. Exposure to constant noise proofed could cause health and well-being problems. Hence, there must be some house adaptations to reduce the noise. This research aims to describe forms of adaptation that Jalan Maleber settlers did in response to high-noise environment situations. Thisresearchis a descriptivequalitative research conducted with interview and observation using therhythm analysis approach. Data werecollectedd by interview and observation, and Samples were chosen by the snowball sampling method. The result showed that noisy conditionsvarious responsesmade by Jalan Maleber Utara settlers. The invention of a new rhythm could achieve Eurhythmiaby every settler in handling noise source rhythm that tends to be a pathology. Even so, arrhythmia could not be avoided,and it could happen if there were no advance action in response to this condition. The intensity of the noise increases, in line with population and economic growth. This research gave a description and solution for noise conditionsin Jalan Maleber Utara Settlement